Umetnost glasbe v času od Monteverdija do Bacha - Snoj, Jurij (ZRC SAZU, Založba ZRC, 2017)
This book ('The art of music in the period from Monteverdi to Bach')is an introduction to the history of Baroque music. It starts by describing seminal innovations in Italian music of the last decades of the 16th century, and terminates by presenting new trends in the music of the first half of the 18th century. The text is divided into twenty chronologically arranged chapters that discuss the most important issues in the development of Baroque music in Italy, Germany, France and England. Each chapter consists of several subchapters that focus on particular topics, such as musical life in specific historical environments, important musical institutions, typical music genres, their origin and development, composers' oeuvres, their biographies, and typical musical forms. Musical genres and composers are illustrated by several dozens of original analytical descriptions of particular musical works. Special chapters are devoted to broader theoretical issues of Baroque music. At the end of the monograph there is a substantial name- and subject index.